Keanekaragaman spesies kutukebul (Hemiptera: Aleyrodidae) pada tanaman hortikultura dengan ketinggian tempat berbeda di Jawa Barat - Nurulalia, Lia; Buchori, Damayanti; Hidayat, Purnama (Perhimpunan Entomologi Indonesia, 2018)
Whitefly (Hemiptera: Aleyrodidae) plays an important role as pest in many horticultural plants (fruits, vegetables, and ornamental plants). The aim of this research was to study whiteflies diversity in horticultural plants on different altitude. Whitefly samples were collected from its host plants in five areas of West Java Bogor, Sukabumi, Cianjur, Bandung, and Garut. The places were grouped into three altitude categories: lowland, midland, and highland. Number of whitefly species and individual were analysed using analysis of variance (ANOVA) with post-hoc Tukey (Î± = 0.05), while the correlation between altitude and whiteflies species number described in linear regression. Species diversity was measured by two types of index (Shannon and Simpson). The highest number of whitefly individual was found in vegetables (121.80). However, the highest number of whitefly species was found in fruits (2.44 species). According to the altitude, the highest number of whitefly species was found in the lowland (4.67 species), whereas the lowest was found in the highland (1.58 species). The abundance of whiteflies population increases with increasing of altitude, whereas the number of species decreases with increasing of altitude. The highest number of whitefly species diversity was found in the lowland (H' = 2.08), meanwhile the lowest was in the highland (H' = 0.38). By contrast, according to the Simpson index, there was species domination of whitefly in the Highland (D = 0.54) by species Aleurodicus dugesii Cockerell